Synthesis and Biological Evaluation of Amidinourea and Triazine Congeners as Inhibitors of MDA‐MB‐231 Human Breast Cancer Cell Proliferation. (23rd January 2017) - Bass, Rosemary; Jenkinson, Sarah; Wright, Jennifer; Smulders‐Srinivasan, Tora; Marshall, Jamie C.; Castagnolo, Daniele
Abstract: A series of novel amidinourea derivatives was synthesized, and the compounds were evaluated as inhibitors of MDA‐MB‐231 human breast cancer cell proliferation. In addition, a second series of triazine derivatives designed as rigid congeners of the amidinoureas was synthesized, and the compounds were evaluated for their antiproliferative activity. Among the two series, amidinourea3 d ( N ‐[ N ‐[8‐[[ N ‐(morpholine‐4‐carbonyl)carbamimidoyl]amino]octyl]carbamimidoyl]morpholine‐4‐carboxamide) emerged as a potent anticancer hit compound with an IC50 value of 0.76 μm, similar to that of tamoxifen. Abstract : New class in the fight : Breast cancer is currently the second most lethal cancer among women, preceded only by lung cancer. Novel amidinourea derivatives were synthesized and evaluated as inhibitors of MDA‐MB‐231 breast cancer cell proliferation. Amidinourea3 d was found to be active against MDA‐MB‐231 breast cancer cells with an IC50 value of 0.76 μm, close to the activity of tamoxifen.